RANCANGAN DATA ASET INVENTORY PADA PT TELKOM AKSES JAMBI - Susanto, Darex (LP2M Universitas Nurdin Hamzah, 2020)
Inventory of goods in a company is one of the company's current assets that is expected to produce maximum profits in the sales process. In order for the sale to proceed as expected, information such as remaining goods, purchase of goods and expenditure of goods must be obtained at any time quickly and accurately. This is very much needed by management in the decision making process that determines the speed of the company's development. Making an information system about inventory that supports the evaluation, analysis and decision making process at the leadership level. For this reason, it is necessary to design a Web- based item data processing, so that it can provide complete information about the inventory asset data through a computerized system. By using the PHP programming language and MySQL database it is expected to be able to handle the asset report.